Therapeutic potential of bimatoprost for the treatment of eyebrow hypotrichosis - Chanasumon N; Sriphojanart T; Suchonwanit P (Dove Medical Press, 2018)
Nongsak Chanasumon, Tueboon Sriphojanart, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand Abstract: Eyebrows serve as a key feature of the face and have many roles, including cosmetic appearance and social communication. Eyebrow hypotrichosis, which refers to reduction or absence of the eyebrow hair, could be a major problem that leads to negative functional, psychological, and social consequences. Bimatoprost is an ophthalmic prostamide analog that is approved by the United States Food and Drug Administration for the treatment of eyelash hypotrichosis. Its proposed mechanism is stimulation of the prostaglandin receptor in dermal papilla and melanocyte, thus leading to a prolonged anagen phase and increased melanogenesis. The hair follicle then increases in thickness, length, and darkness. The efficacy of bimatoprost for the treatment of eyebrow hypotrichosis has been supported by well-controlled studies. Bimatoprost, which is noninvasive, effective, and well tolerated, is worth considering as a treatment option for eyebrow hypotrichosis. Keywords: bimatoprost, eyebrow, hair, hypotrichosis, prostaglandin, prostamide